Policy responses to COVID-19 in Latin American countries: A universal basic income? - Moreno, Dr. María Antonia (Gaceta Médica de Caracas, 2020)
This article describes the implications that adopting a Universal Basic Income (UBI) policy could have in Latin American countries (LAC), based both on the UBI’s analytical considerations and the weak starting socioeconomic conditions that these countries would face in adopting a UBI policy. We conjecture that, given these initial restrictions, the full implementation of a UBI program in the region does not seem feasible at this time; and that, given the profound impact and slow recovery they face in front of the pandemic’s impact, a compromise between a UBI and a less universal and unconditional cash transfer could meet both the need to face the economic emergency in the short term, as well as the financial capacity to address it. En este artículo se describen las implicaciones que la adopción de una política de IBU podría tener en los países de América Latina (ALC), basándose tanto en las consideraciones analíticas del IBU como en las débiles condiciones socioeconómicas de partida a las que se enfrentarían estos países al adoptar una política de IBU. Conjeturamos que, dadas estas restricciones iniciales, la plena implementación de un programa de IBU en la región no parece factible en este momento; y que, dado el profundo impacto y la lenta recuperación a la que se enfrentan ante el impacto de la pandemia, un compromiso entre el IBU y una transferencia monetaria menos universal e incondicional, podría satisfacer tanto la necesidad de hacer frente a la emergencia económica a corto plazo, como la capacidad financiera para abordarla.